2017
DOI: 10.1038/cr.2017.94
|View full text |Cite|
|
Sign up to set email alerts
|

Cryo-EM structure and biochemical analysis reveal the basis of the functional difference between human PI3KC3-C1 and -C2

Abstract: Phosphatidylinositol 3-phosphate (PI3P) plays essential roles in vesicular trafficking, organelle biogenesis and autophagy. Two class III phosphatidylinositol 3-kinase (PI3KC3) complexes have been identified in mammals, the ATG14L complex (PI3KC3-C1) and the UVRAG complex (PI3KC3-C2). PI3KC3-C1 is crucial for autophagosome biogenesis, and PI3KC3-C2 is involved in various membrane trafficking events. Here we report the cryo-EM structures of human PI3KC3-C1 and PI3KC3-C2 at sub-nanometer resolution. The two stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 30 publications
3
50
0
Order By: Relevance
“…Recent studies of the class III PI3K complexes have highlighted the importance of their regulatory and accessory partners in membrane anchoring (Ma et al, 2017;Rostislavleva et al, 2015;Tan et al, 2016). The absence of known regulatory partners for PI3K-C2a and other class II family members, however, has limited our understanding of how this class of PI3Ks are recruited to the membrane, although it has been assumed that their unique PX-C2 modules will play an important role in this process (Campa et al, 2015;Falasca and Maffucci, 2007;Foster et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of the class III PI3K complexes have highlighted the importance of their regulatory and accessory partners in membrane anchoring (Ma et al, 2017;Rostislavleva et al, 2015;Tan et al, 2016). The absence of known regulatory partners for PI3K-C2a and other class II family members, however, has limited our understanding of how this class of PI3Ks are recruited to the membrane, although it has been assumed that their unique PX-C2 modules will play an important role in this process (Campa et al, 2015;Falasca and Maffucci, 2007;Foster et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The class III PI3K Vps34 is also localized via its accessory subunits as part of a multi-subunit complex including Vps15, Beclin-1, and ATG14L (Simonsen and Tooze, 2009). Recent structures of Vps34 complexes further revealed that membrane anchoring occurs via two arms of the complex between Beclin-1, ATG14L, and the kinase domain of Vps34 (Ma et al, 2017;Rostislavleva et al, 2015). In contrast, PI3K-C2a and other class II PI3Ks are generally considered to function as isolated enzymes, lacking known regulatory or accessory subunits to promote membrane targeting (Campa et al, 2015;Falasca and Maffucci, 2007;Foster et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Cryo-EM Structure of the BECN1-MIT-Fusion Complex. Previous EM analyses of PI3KC3s have been limited by the dynamic character of these complexes and by their tendency to be in preferred orientations on EM grids (11,17,25,26). Even when preferred orientations can be reduced or eliminated, the dynamics of the catalytic right arm of the complex (27) has still limited analysis (14).…”
Section: Characterization Of Pi3kc3-c1 Containing a Nrbf2-mit-becn1 Fmentioning
confidence: 99%
“…Previous EM analyses of PI3KC3s have been limited by the dynamic character of these complexes and by their tendency to be in preferred orientations on EM grids (11,17,25,26).…”
Section: Cryo-em Structure Of the Becn1-mit-fusion Complexmentioning
confidence: 99%